Monitoring Tekanan Freon dan Beban Arus Kompresor Untuk Menjaga Efisiensi Kinerja Pendingin Ruangan (AC) Berbasis Internet of Things (IOT) - I Made Fredy Nuryasa; Agus Hayatalfalah; Indah Sulistiyowati; Ahmad Ahfas (TIN: Terapan Informatika Nusantara, 2026)
This study aims to develop an IoT-based monitoring system for Split AC units to track refrigerant pressure, compressor current load, and room temperature in real-time, enhancing operational efficiency and supporting preventive maintenance. The system is designed using an Arduino Nano as the main processing unit and an ESP8266 module for wireless communication integrated with the Blynk platform. A pressure transmitter measures refrigerant pressure, an ACS712 5A current sensor monitors the compressor load, and a DHT22 sensor records room temperature. Test results show that the pressure sensor has a maximum deviation of less than 0.1 psi compared to a manifold gauge, the ACS712 current sensor shows an average difference of 0.03 A compared to a clamp meter, and the DHT22 temperature sensor has a maximum deviation of 0.4 °C compared to a reference thermometer. All sensor data were consistently displayed on the LCD and Blynk application, confirming reliable data transmission. The system can detect anomalies in pressure and current based on manufacturer-specified thresholds, potentially reducing early failure risks, improving energy efficiency, and extending the lifespan of AC units.